Efficiency and safety of single dose Magnesium sulphate in eclamptic convulsion - Goudar, Vinaya; Naganagoudaru, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: An acute and life-threatening complication of pregnancy is characterized by the appearance of tonic clonic seizures, in a patient with pre-eclampsia. Objective of the study was to study the efficacy and safety of a ‘single dose’ of magnesium sulphate in treatment of eclamptic convulsions. Methods: The present prospective study was undertaken among women aged between 18-35 years outpatient’s Department of gynecology in Karnataka Institute of Medical Sciences (KIMS) Hubli, Karnataka, India. The study was undertaken during December 2009 to November 2010. Results: The incidence of eclampsia in our study was 2.12%. Eclapmsia is more common in patients from rural (89%) as compared to urban areas (11%) in our study. In our study eclampsia is more common in unbooked cases (80%). Majority of patients (72%) in our study group were illiterates. 61%, 28% of patients had antepartum and intrapartum eclampsia respectively in our study. We had only 11 post-partum convulsions Table 2. 80% of patients in our study were more than 28 weeks of gestations. 65% of the patients had <5 episodes of convulsions. The number of convulsions did not affect the recurrence, and 35% had >5 episodes. In present study 5 Patients had Systolic Blood Pressure less than 140 mmHg. Majority (52) had more than 160 mmHg 42 had in between 140 and 160 mmHg. Diastolic arterial pressure was >110 in 81% of cases. The convulsions were controlled in 75% of women. Recurrence of convulsions occurred in 25% of women after receiving the single dose magnesium sulphate regime. In our study 75% of cases, there was no recurrence of convulsions and in 25% of cases, there was recurrence of convulsions, out of which 20 cases received low dose magnesium sulphate regime and the other 5 cases received Phenytoin regime as 2nd line of treatment. Conclusions: Hence the single dose Magnesium sulphate is safe and effective in controlling convulsions.